Streamflow response to clear‐cut logging on British Columbia's Okanagan Plateau. Issue 2 (March 2017) - Winkler, Rita; Spittlehouse, Dave; Boon, Sarah
Abstract : The Upper Penticton Creek watershed experiment has collected 28 years of streamflow data from 2 small snow‐dominated watersheds on the Okanagan Plateau of British Columbia, where the effects of timber harvesting on streamflow regime are of broad concern. We apply 3 empirical analysis techniques to these data to evaluate changes in streamflow regime following clear‐cut logging of 47% of the 241 Creek watershed, with the adjacent 240 Creek watershed serving as an unlogged control. While logging had only a small effect on annual yield (5% increase), the results of all 3 analysis techniques confirmed a dramatic change in the timing and magnitude of April through June streamflow. A paired watershed analysis showed that during the first 7 years post‐logging, average April and May water yield increased by 29% and 19%, respectively, while June and July water yield decreased by 23% and 17%, respectively. This pattern of change was confirmed by significant increases in standardised April–May monthly total water yield. Changes in the daily flow duration curves for each month also show a 67% increase in daily yields exceeded ≤10% of the time in April and a 15% increase in May. Daily yields exceeded ≤10% of the time decreased by 24% in June and 17% in July. These streamflow shifts increase the risk of channel destabilization and damage to aquatic habitat during the snowmelt season, and water shortages in the Okanagan region early in the irrigation season (June through July).